Transmitting knowledge a duty - Abd Razak, Dzulkifli (2005)
ANDALUSIAN civilisation reached its apogee in Cordoba where the attitude to learning was just as essential as the Social and cultural dimensions embodied in its rich libraries. The attitude was about the duty to transmit knowledge from one generation to another and about die interplay between the different modes of learning — modes that might contradict each other, as faith and reason did, and do now. These sat happily in the libraries, side by side, unafraid of the contradictions. Firstrate, noted Menocal, a Yale professor in Spanish and Portuguese who wrote a fascinating book about Andalusia entitled The Ornament of the Worlds. Librarians had risen to such administrative and cultural power (as they were frequently authors and scientists as well) that such posts were exclusive to the most wealthy and powerful families.